IDENTITY OF KECAK TOURISTIC PERFORMANCE IN ULUWATU TEMPLE - Putra Kencana, I Putu Adis; Mudana, I Gede; Ardini, Ni Wayan (Journal of Music Science, Technology, and Industry, 2020)
Touristic performances at Uluwatu Temple have some differences in other tourist attractions, so this research was conducted aimed at providing information or an overview of identity in tourist performances at Uluwatu Temple itself. This study uses qualitative methods that prioritize objectivity and honesty in gathering data so that the results obtained will be truly based on research. The results obtained from this study are the performing arts tour in Uluwatu Temple has an identity and characteristics on the presentation. The presentation is good in terms of a strategic place with views of cliffs, the sea, and sunsets, a unique presentation mode spiced with jokes that gives an interesting impression on the presentation. Likewise with the attractions that are served, such as Hanoman dancers who rise above the temple and the scene when burned. All of that has its own charm in this show at Uluwatu. This show is very different from ones in other places.